Analysis of Subtype, Molecular Clusters and Drug Resistance in Newly Diagnosed Individuals with HIV-1 Infection in Jiaxing City, Zhejiang Province, China in 2023 - Ganglin Ren; Xiaofei Zhang; Zhijian Ge; Yamei Zhou; Shencong Lv; Yin Song; Jimei Ji; Lina Li; Yong Yan; Guoying Zhu (Microbiology Research)
The analysis of the molecular epidemiological characteristics of newly diagnosed HIV-infected patients in Jiaxing City is essential for developing effective HIV prevention. Blood samples were collected from newly diagnosed HIV-infected individuals in Jiaxing City from October 2022 to October 2023, and the HIV-1 pol region gene was amplified and sequenced. These sequences were used to construct a molecular transmission network and analyse transmitted drug resistance mutations. We identified 11 subtypes, of which CRF07_BC and CRF01_AE were the most prevalent. The rate of surveillance drug resistance mutation (SDRM) sites in newly diagnosed cases was 9%. A total of 37 molecular transmission clusters were identified, the largest of which was the CRF07_BC-1 cluster (13 nodes). This cluster has five probable high-risk transmitters. Two additional larger clusters in the molecular network were the heterosexual transmission clusters for middle-aged and older males, CRF08_BC-1 (eight nodes) and CRF85_BC-1 (eight nodes). The mean degree of the two clusters was high, and the patients were high-risk transmitters, indicating a higher risk of HIV transmission. The distribution of HIV-1 subtypes in Jiaxing City was widespread, with moderate levels of transmission resistance. Larger molecule clusters carry a high risk of transmission, indicating that we should strengthen monitoring and intervention.